THEORETICAL AND METHODOLOGICAL ASPECTS OF CREATING OF GEOLOGICAL AND GEOPHYSICAL MODEL OF HYDROCARBON FIELDS - Kuzmenko, T.; Tyschenko, A.; Kuzmenko, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New aspects of geological and geophysical models constructions of hydrocarbon reservoirs are considered and outlined the prospect of models application in the modern exploration process. The history of the concepts and methods of geological and geophysical constructions models were analyzed. The approaches focused on automating the entire process of analysis and information processing starting from seismic data processing, interpretation ending with model construction of an area or a field and exploitation are characterized. The classification of geological and geophysical models on the exploration stage is described.